The cost of water politics - Ujang, Azman (The Sun, 2013)
THE revelation by a cabinet minister last week that the country would have saved at least RM700 million had the Selangor government not dragged its feet in approving the Langat 2 water treatment plant is enough to cause us to miss many heart beats.